Intravascular Papillary Endothelial Hyperplasia (Masson's Tumor) as a Rare Entity on Upper Lip: A Case Report and Review - Lakshmi Shetty; Shreya Jeetendra Raut; Gauri Camblay; Tirtha Raj Brahma (Wolters Kluwer Medknow Publications, 2024)
Masson's tumor is a benign intravascular lesion of proliferating endothelial cells that accounts for 2% of vascular and subcutaneous lesions. It manifests clinically as a bluish swelling, resembling a mucocele or hemangioma. Intravascular papillary endothelial hyperplasia (IPEH) was coined by Clearkin and Enzinger in 1976 to describe reactive vascular expansion, following traumatic vascular stasis mimicking angiosarcoma. Clinically, this condition manifests as a bluish enlargement resembling a mucocele or hemangioma. We reported a rare case of IPEH located on the upper lip in an 18-year-old female. A diagnosis of IPEH was reported based on the histopathological findings of papillary proliferating endothelial cells with engorged red blood cells. There was no evidence of recurrence after 6 months of follow-up.